Vegetation Community Convergence of Pastoralists' Pasture at Different Economic Levels in Desert Steppe - Yan-ting YIN; Ji-zhou REN; Xiang-yang HOU (Journal of Integrative Agriculture)
Vegetation characteristics of pastoralist households' pastures at different economic levels were quantified to compare the grassland conditions in Sunite Right Banner, Inner Mongolia, China in 2011 and 2012. The results showed that the heights of Stipa klemenzis and Cleistogenes songorica were similar among economic treatments. And the height of Allium polyrhizm had no significant differences between high-economic-level (HEL) and low-economic-level (LEL) treatments. There were no significant difference among treatments in the canopy cover of C. songorica. The densities of dominant species (S. klemenzis, C. songorica and A. polyrhizm) were significantly similar among treatments. Aboveground community biomass in reference area (CK) was higher than that in other three treatments in 2011, but their biomass showed no significant difference among three economic treatments; for 2012, biomass in HEL was higher than low-economic-level treatment (LEL), while the biomass in middle-economic-level treatment (MEL) and CK was similar to that in HEL and LEL, respectively. Aboveground biomass of S. klemenzis and C. songorica was similar among treatments in both 2011 and 2012. Biomass of A. polyrhizum had no significant difference between HEL and MEL. Households of LEL had rented out excess lands and those of HEL had leased their available lands thus resulting uniform utilization and convergence of pastoralist households' pastures across all economic levels.